Malaysia : Financial Sector Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
This assessment is a review of the financial environment of Malaysia. Like many other Asian countries, Malaysia experienced financial distress in the late 1990s, but the country's policy reforms have moved it to a successful economy. A ten-year financial plan (2001-10) by Bank Negara Malaysia restructured the financial sector. Banks were well capitalized, household debts were strengthened, and securities and insurances were developed. Malaysia thus became the global center for Islamic finance. The authorities look on to a developed Malaysia by 2020.